Gambaran Faktor Risiko Terjadinya Infeksi pada Ibu Hamil di RSUD Prof. Dr. Margono Soekarjo Purwokerto - Devi Verani; Linda Yanti; Surtiningsih; Dita Afika Nurjannah (Akademi Keperawatan Yarsi Samarinda, 2026)
Pregnancy causes anatomical, hormonal, and immunological changes that increase maternal susceptibility to infections, contributing to maternal and fetal morbidity and mortality. This study aimed to describe the risk factors for infections in pregnant women at RSUD Prof. Dr, Margono Soekarjo Purwokerto in 2024. This study used a desciptive quantitative design with a retrospective approach through medical record data, using a total sampling technique of 123 respondents. The variables studied included types of infection, age, education, gravida, body mass index (BMI), blood pressure, and fetal position, with univariate analysis presented as frequency distributions and percetages. The results showed that that the most common infection was urinary tract infection (44,7%), followed by dengue hemorrhagic fever (9,8%), bacterial vaginosis (8,9%), and other infections. Most respondents were aged 20-35 years (80,0%), had basic education (43,5%), and were gravida (91,3%0. The majority had normal BMI (48,7%), normal blood pressure (61,75), and longitudinal fetal position (99,1%). It can be concluded that infections in pregnant women are still commonly found despite mostly normal clinical conditions, indicating the need to improve health education and antenatal care services.